The Effectiveness of Patrol Implementation by the Padang Police Traffic Unit in Combating Wild Racing - Junaidi, Andes; Susi Delmiati; Fahmiron (Master of Law Program, Ekasakti University, 2024)
One of the efforts made to prevent Kamtibmas disturbances by the Police is to conduct patrols, which are regulated in the Regulation of the Head of the Security Maintenance Agency of the National Police of the Republic of Indonesia Number 1 of 2017 concerning Patrols. This is important because it is an essential need for everyone in various aspects of life, and is free from all worries, threats, disturbances of kamtibmas. One of the triggers for kamtibmas disturbances is the wild racing action that occurred in Padang City. Research is descriptive analytical with a normative juridical approach supported by an empirical juridical approach. Based on the results of research and analysis obtained first, the effectiveness of the implementation of patrols by the Padang Police Traffic Unit in tackling wild racing has not been maximally proven until now there are still wild racing actions at several road points in Padang City. In addition, the actions of the Police only use repressive measures, namely fines based on traffic violations. Second, the obstacles encountered in the implementation of patrols by the Padang Police Traffic Unit in tackling wild racing include internal obstacles , namely the absence of a Special Unit that handles wild racing actions so that it is limited to control and disbandment, as well as the lack of personnel of the Padang Police Station considering the large number of illegal racing actors who often move around in holding wild racing actions. External constraints are the absence of integrated cameras with traffic units at road points that are used as wild racing actions so that patrols must still be carried out directly to areas prone to wild racing and betting culture among people who love speed racing and the absence of special facilities and places or racing arenas in Padang City.